Adjuvant TKIs: still an optimal choice - Liu, Si-Yang; Wu, Yi-Long (Journal of Thoracic Disease, 2018)
Thanks for Pro. Hai-Quan Chen and colleagues for their interest in our study and appreciate it raises questions about the trial design and eventual OS benefits for EGFR mutant patients received adjuvant TKI therapy (1).